Mean flow properties for equatorially trapped internal water wave–current interactions. Issue 13 (3rd October 2017) - Rodríguez-Sanjurjo, Adrián; Kluczek, Mateusz
Abstract : The aim of this paper is to provide an analysis of the mean flow velocities, and the related mass transport induced by equatorially trapped internal water waves with a constant underlying current.